UNDERSTANDING THE RISK FACTORS ASSOCIATED WITH VIOLENT BEHAVIOR IN SCHIZOPHRENIA - Zdravkovic, Miodrag; Petrović, Jovana; Binic, Iva; Tošić Golubović, Suzana; Petrovic, Filip; Pinterovic, Bogdan (Acta medicae Medianae, 2026)
This review examines the risk factors associated with violent behavior in individuals with schizophrenia, highlighting public perceptions and empirical evidence in this area. While schizophrenia affects approximately 1% of the population, research indicates that 5% of homicide offenders have been diagnosed with the disorder. Public stereotypes link mental illness with aggression, yet studies show only a modest association between schizophrenia and violent behavior. Proposed risk factors include younger age, male gender, unemployment, economic disadvantage, childhood abuse, and poor anger management. Substance misuse, particularly among individuals with schizophrenia, significantly increases the risk of violence, while the duration of untreated psychosis is also correlated with a higher likelihood of violent behavior. Individuals experiencing first-episode psychosis face an elevated risks of violence prior to receiving treatment. Research indicates that symptoms such as hallucinations and delusions correlate with aggressive behavior, with personality disorders, particularly antisocial personality disorder, identified as significant predictors. It is important to note that while individuals with schizophrenia typically demonstrate lower rates of violence, the existence of comorbid conditions or acute psychotic symptoms can markedly increase the associated risk. Early identification and appropriate treatment can help reduce these risks and improve community safety.